2007
DOI: 10.1002/yea.1570
|View full text |Cite
|
Sign up to set email alerts
|

A Saccharomyces cerevisiae cell‐based quantitative β‐galactosidase assay compatible with robotic handling and high‐throughput screening

Abstract: Reporter-gene assays that employ the Escherichia coli lacZ gene are ubiquitously employed in biological research. However, we were not able to readily identify a quantitative method that worked reliably with yeast (Saccharomyces cerevisiae) cells and that was compatible with high-throughput screening and robotic liquid handling tools. We have therefore adapted a commercially available assay employing a 6-O-β-galactopyranosyl-luciferin substrate to provide the required sensitivity with minimal sample handling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…Measurement of β-galactosidase activity after overnight yeast growth showed that, as previously observed, 27 the mutant eIF2B strain gave at least twofold higher get uniform mixing in these plates. Therefore, we decided to grow cells in V-bottom polypropylene plates.…”
Section: Assay Development and Validationsupporting
confidence: 83%
See 4 more Smart Citations
“…Measurement of β-galactosidase activity after overnight yeast growth showed that, as previously observed, 27 the mutant eIF2B strain gave at least twofold higher get uniform mixing in these plates. Therefore, we decided to grow cells in V-bottom polypropylene plates.…”
Section: Assay Development and Validationsupporting
confidence: 83%
“…The assay was optimized for HTS by adaptation of a commercially available coupled β-galactosidase-fi refl y luciferase system for use with yeast cells. 27 Mutant and wild-type yeast strains were screened in parallel to identify compounds acting specifi cally on either strain. The parallel screening strategy was designed to eliminate nonspecifi c compounds directly following HTS and thereby minimize the number of cherry-picks required.…”
Section: Preparation Of Yeast Stocksmentioning
confidence: 99%
See 3 more Smart Citations